Post traumatic stress disorder and complex post-traumatic stress disorder reflected in Always Watching by Chevy Stevens - Yudha Hari Pamungkas Saja; Linusia Marsih (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. Stress Disorder experienced by the two main characters, Nadine and Heather, in Always Watching by Chevy Stevens. The discussion focuses on the PTSD suffered by Nadine, CPTSD suffered by Heather, the effect of Nadine’s PTSD to ward her life, and the effect of Heather’s CPTSD to ward her life. This research applies descriptive qualitative method due to that fact the data is discriptive and the data analysis is presented disciptively. In addition, psychological approach is applied in this study because the study deals with the psychological aspects of the characters in the novel. The analysis shows that Nadine suffers from PTSD due to the traumatic event in her childhood. Nadine’s PTSD is indicated by several symptoms i.e. avoidance of stimuli associated with the traumatic experience and anger, flashback to the traumatic event, blaming and feeling guilty, excessive alertness and overreaction to anything. Further, Heather suffers from CPTSD. There are several symptom to indicate that Heather suffers from CPTSD i.e. always being nervous, crying, being easily angry, having disturbed images of thoughts, decreasing desire to act and communicate with the surrounding environment, feeling of isolation from others, blaming and guilty, hypervigilance, fear, anger or hopelessness, and suicidal thoughts, plans or attempts. The PTSD suffered by Nadine makes her experience trust issue and anxiety. Moreover, the CPTSD suffered by Heather makes her to get difficalty socialiling with others, easly angry, and nervous.